O adoecimento pelo cancer de laringe The illness narrative for larynx cancer - Márcia Maria Fontão Zago; Elizabeth Barichello; Sabrina Hannickel; Namie Okino Sawada (SciELO, 2001)
Com a finalidade de aprimorar a assistência ao laringectomizado, este estudo teve o objetivo de compreender o adoecimento pelo câncer de laringe na visão do paciente e sua família. Participaram do estudo 14 pacientes laringectomizados e familiares, em diferentes períodos pós-operatórios. Na análise das narrativas identificamos categorias que foram interpretadas sob a visão antropológica da cultura. Na interpretação dos participantes, o processo é permeado pelo sofrimento, pela busca de estratégias de enfrentamento, pela valorização de sobreviver à cirurgia, ou seja, pressupostos culturais que diferem do modelo biomédico dos profissionais e que devem ser considerados na sua reabilitação. With the purpose of improving the care of laryngectomized patients, the aim is to understand the illness experience of patients and families of having larynx cancer. The participants were 14 laryngectomized patients and their families, in different post-surgical periods. The narrative analysis searched for categories which were understood on the basis of an anthropological focusing the culture. The understanding that the participants had of the illness experience of having a larynx cancer shows us that this process is one of suffering, of searching of strategies of coping, of evaluating the survival to the surgical treatment, which were based on the cultural system, which is different from the biomedical model of the health professionals and they must be considered in the approach for the rehabilitation.